Resilient Graph Partitioning for Quantum Networks - Menina, Abdelkrim; Tunc, Hilal Sultan Duranoglu; Yilmaz, Ayse Nur; Bassoli, Riccardo; Fitzek, Frank H.P. (Institute of Electrical and Electronics Engineers Inc., 2024)
Quantum entanglement is important for quantum communications for long range transmission. Such long transmission is achieved through entanglement swapping, a method monopolizing considerable resources as the quantum network topology expands. Therefore, in this work we propose a method to reduce the resources required for entanglement swapping using network partitioning while ensuring resiliency. This method involves the fidelity of distributing entangled states that depends on the source, the link and the bell state analyzer utilized to quantify the required fidelity for a functioning network. By partitioning the network to redundant sub-graphs, we show the advantage of such approach in reducing the required functional fidelity.
Keywords: Network Partitioning; Resiliency